Fixed Rate or Index-Linked Mortgages from the Borrower's Point of View: A Note - Statman, Meir (Journal of Financial and Quantitative Analysis, 1982)
When will borrowers choose fixed rate mortgages and when will they prefer index-linked mortgages? Baesel and Biger (BB) [1] proposed a model that answers this question. According to the BB model, a borrower's preference depends on the difference in interest rates between the fixed and index-linked mortgages, and on the covariance between the borrower's labor income and the rate of inflation. The purpose of this note is to propose a more complete model of borrower preferences. The novelty of the model lies in the inclusion of the value of the house (net of mortgage obligation) in the terminal wealth of the borrower. This inclusion leads to differences between this model and the BB model in the identification of the cases where borrowers will prefer fixed or index-linked mortgages.